The Effects of Remittances on Output per Worker in Sub-Saharan Africa: A Production Function Approach - John Ssozi; Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
This paper uses a production function to examine the channels through which remittances affect output per worker in 31 Sub-Saharan Africa (SSA) countries from 1980-2010. We find that remittances directly increase output per worker if complemented with education. The indirect effects vary with the economic characteristics of the recipient nations: while remittances have increased human capital among the low-income nations, among the upper-middle-income nations, they have mostly increased total factor productivity, but are still inversely related to factor inputs among the lower-middle-income nations of SSA. Finally, remittances are more effective when institutional risk is reducing.
Keywords: F22; F24; F35; F43; F63; O15; O16; O43; O55; 330; remittances; output per worker; total factor productivity; Sub-Saharan Africa